2022
DOI: 10.3389/fonc.2022.1005042
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with mismatched unrelated donor allogeneic hematopoietic stem cell transplantation in adults: A systematic review and meta-analysis

Abstract: BackgroundAllogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy for various hematologic disorders. Alternative donor strategies such as mismatched unrelated donors (MMUD) offer the option of HSCT to patients lacking a human leukocyte antigen (HLA)-matched donor. We conducted a systematic review and meta-analysis to evaluate outcomes after MMUD-HSCT.MethodsA literature search was performed on PubMed, Cochrane Library, and ClinicalTrials.gov from the inception date through A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, the survival of individuals who have undergone allo-HSCT is also affected by the compatibility of specific HLA loci of the donor and recipient. A recent publication pointed out that HLA matching and the age of the recipient are simple factors that can accurately stratify subjects into prognostic groups as well as predict overall survival and non-relapse mortality in allo-HSCT[ 180 ]. However, a meta-analysis of 19 investigations with a patient sample of 3336 individuals concluded that mismatched allo-HSCT from unrelated donors remains a safe procedure that is linked with favorable outcomes[ 181 ].…”
Section: Intervention and Treatment Strategies For Post-allo-hsct Rel...mentioning
confidence: 99%
“…In addition, the survival of individuals who have undergone allo-HSCT is also affected by the compatibility of specific HLA loci of the donor and recipient. A recent publication pointed out that HLA matching and the age of the recipient are simple factors that can accurately stratify subjects into prognostic groups as well as predict overall survival and non-relapse mortality in allo-HSCT[ 180 ]. However, a meta-analysis of 19 investigations with a patient sample of 3336 individuals concluded that mismatched allo-HSCT from unrelated donors remains a safe procedure that is linked with favorable outcomes[ 181 ].…”
Section: Intervention and Treatment Strategies For Post-allo-hsct Rel...mentioning
confidence: 99%
“…Previous published studies have reported a higher incidence of GvHD and non-relapse mortality (NRM) in the setting of MMUD HCT [ 12 ]. Recent improvements in supportive care, HLA typing and GvHD prophylaxis, including PTCY, have resulted in better survival outcomes and acceptable toxicity profile after MMUD [ 13 ]. In the last years the traditional use of ATG in combination with calcineurin inhibitor and mycophenolate mofetil for 9/10 MMUD HCT has been overtaken by the progressive use of PTCY in this platform in different European institutions.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing advancement in diagnostic modalities and improvement in HSCT outcomes, an increasing number of patients are now being considered for HSCT [ 2 ]. Finding a human leukocyte antigen (HLA)-compatible donor remains one of the limiting factors, hampering the utilization of HSCT [ 3 ]. However, the advent of newer transplant strategies has resulted in a global increase in haplo-identical HSCT.…”
Section: Introductionmentioning
confidence: 99%